ANALISIS UNSUR INTRINSIK DALAM NOVEL IBU, DOA YANG HILANG KARYA BAGAS D. BAWONO - Apriyanti, Mariana; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe and analyze the intrinsic elements found in the novel, Ibu, Doa yang Hilang by Bagas D. Bawono. The method in this study is descriptive, qualitative forms and structural approaches. Data in the form of sentences relating to the problem under study, namely intrinsic elements include the stages of flow, the types of settings, the function of the appearance of characters and characterizations, and the message contained in the novel. The data source in this research is the novel, Ibu, Doa yang Hilang by Bagas D. Bawono. The technique used is documentary study technique. The data collection tool is the researcher herself as the main instrument.The results of this study are: 1) the stages of the flow include the stages of introduction or the stage of introduction, the stage of occurrence of conflict or conflict, the stage of increasing conflict, the climax stage, and the stage of completion. 2) the types of backgrounds include the setting of the place, time, and social setting. 3) the function of character appearance and characterization to explain the role of protagonist and antagonist 4) the message contained in the novel, education is important for the future of children. This research can be applied by Indonesian language teachers in providing teaching material about the analysis of intrinsic elements in novels in class XII of even semester. Keywords: Analysis, Intrinsic Elements, Novel